The Effect of Using Pattern Guide Strategy on the Students’ Reading Comprehension in Narrative Text - Syahreza Andika Gunawan (Utamax : Journal of Ultimate Research and Trends in Education, 2020)
The students in the eighth grade of MTs Imam Ibnu Katsir Pekanbaru had some phenomena in reading. First, the students got difficult in understanding the social function. The second, the students got difficult in understanding the grammar in narrative text. Concerning the syllabus of MTs Imam Ibnu Katsir Pekanbaru, the students’ comprehension of social function, generic structure, and language features in narrative writing. This research aims to identify the effect of pattern guide strategy on the students' reading comprehension in narrative text. This research was conducted at the eighth-grade students of MTs Imam Ibnu Katsir Pekanbaru in January 2018. The research design used quasi-experimental research. The samples of this research were the students of class VIIIa consisting of 25 students and class VIIIb composed of 22 students. The data were collected by pre-test and post-test. Then, it was analyzed statistically by using SPSS verse 16.0. Then, the data were calculated by using N-Gain between pre-test and post-test in the experimental class. After conducting this research, the result of this research was that the post-test score of the experimental class was getting higher than the pre-test score. It can be seen from the average post-test score of the experimental class was 71.40, which improved from the pre-test score 56.80. The average post-test on the control class was 66.36 was lower than the experimental class. In conclusion, it can be stated that the students who are taught using pattern guide strategy achieve better than those who are not taught using pattern guide strategy.